Questioning in teaching of Early Mathematics: A Review - BHUSHAN, SATYA (THE PRIMARY TEACHER, 2016)
Questioning is a powerful instructional strategy. Those interested in mathematics education have recognised the value of asking relevant questions for centuries. Classroom questioning is an extensively researched topic. Teachers use questioning fundamentally to check the understanding and knowledge of students to aid teaching, diagnose students’ difficulties, recall facts, test their knowledge after the lesson is over, direct attention and maintain control. The high incidence of questioning as a teaching strategy and its consequent potential for influencing learning have led investigators to examine relationships between questioning methods and student achievement. The present review focuses on the importance of classroom questioning in the teaching-learning process in early mathematics